Živeti in stanovati v osmanskih mestih Bosne in Hercegovine - Avžlahar, Alenka (Etnolog. Nova vrsta (Ljubljana), 2003)
The article presents the findings of a research into the principal characteristics of Ottoman urbanism, the typical topography of Ottoman towns, and the dwelling culture of town inhabitants in Bosnia and Herzegovina under the Ottoman Rule. The research was carried out by studying and analysing the available professional literature and travel books.
Keywords: ethnology; etnologija; mesta; etnologija mest; Bosna in Hercegovina; Bosnia and Herzegovina; način življenja; zgodovinski pregledi